Research on Positive Youth Development-focused Coach Education Programs: Future Pathways and Applications - Santos, Fernando (2018)
Research on positive youth development (PYD)-focused coach education programs have provided valuable insights on how to increase youth sport coaches’ ability to facilitate PYD. Variables such as key program stakeholders’ behaviors (e.g., parents) and course instructors’ behaviors, however, have not been studied. This paper offers suggestions for conceptualizing and organizing research on PYD-focused coach education programs and interventions that expand beyond coaches. Specifically, research on PYD-focused coach education programs should consider including sport leaders and parents in such interventions, and provide training for coach instructors to teach youth sport coaches how to facilitate PYD. Conducting this type of research will help researchers have greater real world impact and facilitate an understanding of the sustainability of PYD behaviors